Soft‐switching DC–DC Cuk converter operating in discontinuous‐capacitor‐voltage mode. Issue 13 (1st August 2017) - Poorali, Behzad; Adib, Ehsan; Farzanehfard, Hosein
Abstract : This paper proposes an improved topology for the conventional DC–DC Cuk converter operating in discontinuous‐capacitor‐voltage mode which provides soft‐switching conditions for all the semiconductor devices. The improved topology has only three passive components in addition to the elements of the conventional counterpart, an extra winding, an auxiliary diode, and an auxiliary inductor. Therefore, without using any extra active switch, the soft‐switching operation is attained and the switching losses are reduced. In the proposed converter, the power switch turns on and off under zero‐current‐switching and zero‐voltage‐switching conditions, respectively. In addition, the switch current is reduced in comparison with the conventional Cuk converter resulting in lower current stress. Also, the leakage inductance energy is recycled and continuity of the input and output currents are preserved. It is shown that reduction of the switch current and soft‐switching operation improves the overall efficiency. Analysis of the proposed converter together with the design guidelines is presented. Moreover, the experimental results of a 100 W prototype producing −24 V from 150 V input voltage are provided and compared with the results obtained from a similar prototype of the conventional Cuk converter.